2017
DOI: 10.1002/jcb.25863
|View full text |Cite
|
Sign up to set email alerts
|

The BET Bromodomain Inhibitor JQ1 Suppresses Chondrosarcoma Cell Growth via Regulation of YAP/p21/c-Myc Signaling

Abstract: Chondrosarcoma, the second-most frequent primary bone malignancy, is generally more resistant to conventional chemotherapy and radiotherapy. Therefore, the development of an effective adjuvant therapy is necessary. Recently, targeting the epigenetic regulator such as bromodomain and extraterminal domain (BET) proteins has achieved great success. For instance, the bromodomain inhibitor JQ1 has been shown to inhibit the growth of several cancer cells both in vitro and in vivo. Herein, we demonstrated that JQ1 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 35 publications
6
41
0
Order By: Relevance
“…13 Moreover, the high expression of YAP in neuroblastoma is correlated with tumour grade of neuroblastoma. 13 Consistent with these studies, our results showed that YAP was abundantly expressed in different glioma cell lines, and the expres- There are evidences revealing that YAP can modulate tumour cell proliferation through regulating the expression of cell cycle proteins, such as p27 Kip1 , p21 45 and cyclinD1. 25,28,43 p27 Kip1 is a cyclin-dependent kinases inhibitor that involved in the pathogenesis of neuroblastoma.…”
Section: Discussionsupporting
confidence: 88%
“…13 Moreover, the high expression of YAP in neuroblastoma is correlated with tumour grade of neuroblastoma. 13 Consistent with these studies, our results showed that YAP was abundantly expressed in different glioma cell lines, and the expres- There are evidences revealing that YAP can modulate tumour cell proliferation through regulating the expression of cell cycle proteins, such as p27 Kip1 , p21 45 and cyclinD1. 25,28,43 p27 Kip1 is a cyclin-dependent kinases inhibitor that involved in the pathogenesis of neuroblastoma.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, lovastatin was reported to reduce the survival of Ewing sarcoma cells [260]. Among epigenetic drugs, only JQ1 was previously reported to affect LATS1, YAP and TAZ in chondrosarcoma [182], potentially by restoring suppressed AMOT expression [183] (Figure 4). Among natural compounds, agave extract was reported to downregulate YAP and TAZ mRNA and the protein in osteosarcoma cell lines by a mechanism that still needs to be explored [261].…”
Section: Resultsmentioning
confidence: 94%
“…A recent study identified YAP nuclear accumulation as a consequence of LATS1 inactivation by protein arginine methyltransferase 1 (PRMT1) as an independent bad prognostic factor in chondrosarcoma [181]. Finally, the treatment of chondrosarcoma cells with the BET-bromodomain inhibitor JQ1 downregulated YAP/TAZ and LATS1, leading to the upregulation of cyclin-dependent kinase inhibitor 1a (CDKN1A/p21) and cell cycle arrest, senescence and apoptosis [182]. Potentially, this downregulation was mediated by epigenetic restoration of the expression of the inhibitory YAP/TAZ-binding scaffold protein angiomotin (AMOT) [183].…”
Section: Yap/taz In Chondrosarcomamentioning
confidence: 99%
“…Different concentrations of 17‐AAG (0.05, 0.5, 1, 10, and 50 µM) were added to the cells and incubated for the indicated times. Afterwards, cell counting kit‐8 (CCK‐8, C0038, Beyotime, China) was used to determine the cell viability according to manufacturer's instructions with minor modifications …”
Section: Methodsmentioning
confidence: 99%